Industrial yeasts strains for biorefinery solutions: Constructing and selecting efficient barcoded xylose fermenting strains for ethanol. (7th March 2014) - Tomás‐Pejó, Elia; Bonander, Nicklas; Olsson, Lisbeth
Abstract There have been intense efforts in the scientific community and industry to engineer S. cerevisiae strains to co‐consume xylose and glucose. In this context, this paper describes a process for introducing a barcode into an industrial xylose fermenting yeast strains to ensure quick and reliable identification of patented industrial strains. Furthermore, this work presents a novel procedure for screening and selecting the clones that reflects the characteristics of the industrial process. The key points of efficient selection of high‐performing clones are elaborated and discussed. In spite of the unforeseen effects on yeast physiology after the introduction of a new sequence into the genome, we obtained barcoded clones with the same xylose consumption rates and ethanol yields as the cells without the barcode. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd